Simulation of Behavior of Hotel and Restaurant Business Staff in the Conditions of COVID-19 Viral Pandemic - BOVSH, Liudmіla; HOPKALO, Larysa; LEVYTSKA, Inna; KOMARNITSKYI, Igor; RASULOVA, Alla (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021, 2021)
The research views staff behavior as a complex mechanism of motivators through the lens of rationality, which obeys the principles of the transitivity axiom and the law of declining marginal utility in times of crisis, including the quarantine COVID-19 pandemic, budget constraints. The factors which affect the behavior of hotel and restaurant staff form a field for understanding behavioral responses. The interests and motives that regulate the behavior of the staff, in this case, reflect the map of utility, which allows modeling the usefulness of employment in an enterprise. It is substantiated that the behavior of the staff should be correlated with the influence of leadership and agile management methods (Scrum, Kanban). The Agile determinants in the pandemic client-oriented management of the hotel and restaurant business provide an algorithmic explanation for the application of the approaches in practice. Flexible management methods allow you to create organizational values for staff, which allows you to build value dependencies within cross-functional team management. The result is the consideration of motivational types of staff and methods for choosing the right Agile approach. It also suggested ways to reformat the hotel and restaurant business in the pandemic and change the professional roles of workers to survive and create conditions for rapid rehabilitation and recovery in the post-quarantine period.